Advanced exergy analysis of ash agglomerating fluidized bed gasification. (1st November 2019) - Li, Guang; Liu, Zheyu; Liu, Fan; Yang, Bin; Ma, Shuqi; Weng, Yujing; Zhang, Yulong; Fang, Yitian
Highlights: Advanced exergy analysis is performed for the AFB gasification process. 54.18% of the total exergy destruction can be reduced. The AFB gasifier has great potential for performance improvement. Sensitivity analysis is discussed considering variations in operation conditions. Abstract: Exergy-based analysis is a powerful method to evaluate, understand, and improve energy conversion processes. Compared with conventional exergy analysis, advanced exergy analysis can identify the improvement potential of each component and the interactions among components of the whole system. In this paper, the ash agglomerating fluidized bed (AFB) gasification process is simulated in Aspen Plus (version 8.0). Based on the simulation results, advanced exergy analysis is carried out to study the performance of the AFB gasification process. The exergy efficiency of the AFB gasification process is 82.13% and the total exergy destruction is 4670 kW. The result shows that 54.18% of the total exergy destruction can be avoided. The AFB gasifier has the largest potential for reducing exergy destruction. In addition, sensitivity analysis is performed to research the effects of carbon conversion, pressure and temperature on the exergy destruction of the AFB gasifier.